The effect of antimicrobial peptide gel RISE-AP12 on decreasing neutrophil and enhancing macrophage in nicotine-periodontitis Wistar rat model - Ika Andriani; Ana Medawati; Muhammad Ihza Humanindito; Maulida Nurhasanah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Periodontitis, an inflammation that causes alveolar bone destruction, is caused by bacteria and aggravated by nicotine exposure and is therefore a disease that many smokers have. Antibacterial agents are essential for the rejuvenation process in periodontitis treatment; antimicrobial peptide (AMP) gel is a broad-spectrum antibacterial agent that is hardly cause bacteria resistance. Purpose: The objective of this study is to determine the effect of AMP gel administration on neutrophil and macrophage counts on periodontitis regeneration in nicotine-exposed rats. Methods: 24 Wistar rats were separated into four groups: nicotineexposed, non-nicotine-exposed, treatment and control. Rats with periodontitis were given AMP in the gingival line on days 1, 3 and 7 after having their mandibular central incisors ligated for 14 days to induce periodontitis. After AMP treatment, two groups of rats were collected randomly. Each group were decapitated, followed by treatment and histological examination with hematoxylin-eosin staining in the pathology laboratory to view neutrophils and macrophages. The asymmetric Kruskal Wallis test was used to analyse the data. Results: In mice treated with AMP, neutrophil counts on day 3 were lower than in distilled water (Aquadest) controls. The number of macrophages on day 3 was higher than that of the Aquadest control. Kruskal Wallis test results for neutrophils were p = 0.017 and for macrophages p = 0.01, where both test results had p < 0.05, there were significant differences between the neutrophil and macrophage groups. Conclusion: The administration of AMP effects on decreasing the number of neutrophils and enhancing macrophages in the periodontitis regeneration. in nicotine-exposed rats.